Attenuation of Rayleigh waves by a combined periodic open trench-wave impeding block vibration isolating barrier considering tunnel influence - Hou, Bin; Li, Wenwen; Pei, Junhua (Frontiers in Physics, 2025)
Traditional open trench and wave-impeding block barriers often suffer from narrow vibration isolation bandwidths, and their performance is further affected by tunnel scattering. To overcome these limitations, this study proposes a periodic open trench-impeding block joint barrier that combines Bragg scattering and local resonance to achieve broadband attenuation of Rayleigh waves. A plane strain tunnel-barrier coupling model incorporating Floquet periodic boundary conditions and the finite element method was developed to reveal the mechanisms of bandgap formation and parameter regulation under multi-physical field coupling. Dispersion analysis demonstrates that the proposed barrier produces three bandgaps within 11.3∼67.3 Hz, covering the dominant frequencies of seismic and environmental vibrations. The trench depth-to-width ratio is identified as the primary factor governing low-frequency expansion and mid-to-high-frequency stability through its effects on unit stiffness and Bragg scattering efficiency, while the material properties of the wave-impeding block play only a minor role, thereby supporting a design strategy centered on geometry optimization. Furthermore, tunnel scattering is shown to enhance isolation performance in the mid- and high-frequency ranges, where secondary reflections and phase cancellation lead to a 46% increase in peak transmission attenuation. These findings highlight the synergistic effect of geometric design and tunnel scattering in broadening vibration isolation bandwidth, providing a theoretical foundation for the development of efficient broadband vibration isolation barriers in complex underground environments.